2022
DOI: 10.1186/s12891-022-05811-x
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and composition of the ventral neck muscles in individuals with chronic whiplash related disorders compared to matched healthy controls: a cross-sectional case–control study

Abstract: Background Objective Studies of cross-sectional area (CSA) (morphology) and muscle fat infiltration (MFI) (composition) in ventral neck muscles is scarce in patients with chronic whiplash associated disorders (WAD), especially for men and those with severe WAD compared with matched healthy controls. The aim was to compare CSA and MFI of sternocleidomastoid (SCM), longus capitis (LCA) and longus colli (LCO) in patients with chronic right-sided dominant moderate (Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The voluntary neck muscle's function was not based only on biomechanics 36 , movements were related to the combination of numerous muscles and there were differences between voluntary preferred activation and the measured biomechanical directions. Changes in the muscle's composition on the side of greatest pain was also seen in WAD, with increased fatty in ltration in Sternocleidomastoid in the pain dominant right side but not in the left side 37 .…”
Section: Discussionmentioning
confidence: 85%
“…The voluntary neck muscle's function was not based only on biomechanics 36 , movements were related to the combination of numerous muscles and there were differences between voluntary preferred activation and the measured biomechanical directions. Changes in the muscle's composition on the side of greatest pain was also seen in WAD, with increased fatty in ltration in Sternocleidomastoid in the pain dominant right side but not in the left side 37 .…”
Section: Discussionmentioning
confidence: 85%
“…They have lower neck muscle endurance 36 , altered intermuscular interplay in the neck with less activation of the deep neck muscles and less synchronization between the deep and superficial muscle layers 15 , and impaired sensorimotor function 24 . Moreover, fatty infiltration in the neck muscles (contractile muscle tissue replaced with fat) has been reported in WAD 8 10 , especially in the deep neck muscles which contain many proprioceptors that are important for maintaining the sensorimotor system and balance 11 13 . Individuals with WAD who had a disturbed neck proprioception had to rely on visual feedback for balance performance.…”
Section: Discussionmentioning
confidence: 99%
“…Research studies have shown increased fatty infiltration in WAD 8 10 , especially in the deep neck muscles which contain many proprioceptors that are important for maintaining the sensorimotor system and balance 11 13 . Furthermore, decreased neck muscle endurance, altered sensorimotor function, altered movement pattern and disturbed eye-neck control have been reported 14 24 .…”
Section: Introductionmentioning
confidence: 99%
“…These findings are intriguing and warrant further discussion in the context of current literature on the subject. Several studies have examined the relationship between cervical multifidus muscle morphology and postural balance in different populations, including individuals with musculoskeletal disorders and neurological conditions [23][24][25]. Some of these studies have reported significant associations between cervical multifidus muscle morphology and postural balance, suggesting that alterations in muscle structure could contribute to postural instability [26].…”
Section: Discussionmentioning
confidence: 99%